Color of her panties - Anthony, Piers (New York AvoNova, 1992)
While struggling for the Goblin crown, Gwenny Goblin is forced to compete with her awful half-brother, Gobble, in a battle of wits and enlists the aid of Che Centaur and Jenny Elf to do so. $10,000 ad/promo.
79293
Keywords: Xanth (Imaginary place) -- Fiction; Fantastic fiction